Studies in Oxidation of Gallic Acid - Chauhdary, R.B.; Singh, S.N. (Asian Journal of Chemistry, 2010)
Oxidation of gallic acid with KMnO4 has been investigated and the oxidation product has been characterised by means of physicochemical methods which include analytical, spectral IR and 1H NMR, magnetic and potentiometric measurements. Mechanism for the cleavage of gallic acid by KMnO4has been proposed.